Efficient recovery of phosphate from aqueous solution using biochar derived from co-pyrolysis of sewage sludge with eggshell. Issue 5 (October 2021) - Yang, Jie; Zhang, Mingliang; Wang, Haixia; Xue, Junbing; Lv, Qi; Pang, Guibin
Abstract: A novel Ca-modified biochar were prepared via co-pyrolysis of eggshell and sewage sludge (mass ratio 2:1) for recovering phosphorus from wastewater. The maximum adsorption capacity reached 106.99 mg P/g, and it exhibited good ability for phosphate adsorption from solution in a wide range of pH (2–11) with removal efficiency more than 96% for 50 mg P/L with adsorbent dosage 2 g/L. The co-existing NO3 -, Cl - and SO4 2- did not significantly influence adsorption performance because of the reduction of adsorption capacity less than 5%, except for HCO3 - . Adsorption thermodynamic parameters indicated that adsorption process was spontaneous and endothermic, suggesting that increasing temperature is favorable for the adsorption. Based on the comparison analysis of physico-chemical properties (FTIR, XPS, XRD and SEM-EDS) for biochars before and after phosphate adsorption, electrostatic attraction and precipitate with hydroxyapatite (Ca5 (PO4 )3 (OH)) were main removal mechanisms. The P-laden biochar exhibited excellent ability for phosphorus recovery and application: (1) the P-laden biochar can be used as adsorbent for heavy metal removal from solution. The removal efficiency of Pb 2+, Cu 2+, Cd 2+ and Zn 2+ (5–10 mg/L) reached more than 99% with the absorbent dosage of 2 g/L; (2) the P-laden biochar can be used as slow-release P fertilizer for soil. Pot experiment results showed that it significantly promoted Brassica chinensis germination (increasing by 18.89%) and growth (increasing by 50.62%) compared with control treatment. The utilization of biochar increased soil pH and salt content, so it is essential to determine rational usage amount and long-term monitoring for soil health. Graphical Abstract: ga1 Highlights: Novel Ca-biochars were prepared from co-pyrolysis of solid wastes eggshell and sewage sludge. The Ca-biochar exhibited excellent performance for phosphate recovery from aqueous solution. The Ca-biochar after phosphate adsorption can be reused as adsorbent for heavy metal and slow-release fertilizer. Reveal the mechanisms on phosphate recovery by the synthesized Ca-biochar.